An overview of antimicrobial and antioxidant bioautography method analysis: Cosmos caudatus and Orthosiphon stamineus / Nadia Anuar, Sadia Sultan, Kamran Ashraf - Anuar, Nadia; Sultan, Sadia; Ashraf, Kamran (Faculty of Pharmacy, 2022)
Medicinal herbs such as Cosmos caudatus and Orthosiphon stamineus are sources of a huge number of bioactive compounds with antioxidant and antimicrobial properties. C. caudatus plant has bioactive compounds such as phenolics, flavonoids, and terpenoids. On the other hand, phytochemicals from O. stamineus have been shown to have a wide range of traditional applications due to their antioxidant and antibacterial characteristics. The bioautography method is used to isolate active molecules on chromatogram followed by the chemical and biological detection system. In antimicrobial bioautography, agar overlay Thin Layer Chromatography (TLC) bioautography detection, direct TLC bioautography detection, and contact bioautography are used for antimicrobial screening of the compounds. Meanwhile, TLC 2, 2-diphenyl-1-picrylhydrazylradical (TLC-DPPH) bioautography is applied for the detection of antioxidant activity of the plant extracts. This review aims to list and describe the antimicrobial and antioxidant bioautographic methods used especially for C. caudatus and O. stamineus plants. This study might be useful in identifying the antimicrobial and antioxidant properties of the constituents of both plants.